Enhancing Writing Skills in Slow Learners Through Differentiated Learning and Audio-Visual Media: A Classroom Action Research in Indonesian Elementary Education - Kamsiah, Kamsiah; Pujaningsih, Pujaningsih (Journal of Innovation and Research in Primary Education, 2025)
Writing difficulties among slow learners present significant challenges in inclusive elementary education settings. This study investigated the effectiveness of combining differentiated learning strategies with audio-visual media to enhance writing abilities among fifth-grade slow learners. A participatory classroom action research design was employed using the Kemmis and McTaggart spiral model across two intervention cycles. The study was conducted at SD Negeri 003 Sandaran, East Kalimantan, Indonesia, with one primary slow learner participant (IQ 75-89) from a class of 31 students. Data collection involved pre-test and post-test assessments, structured observations of learning activities and student participation, and documentation of instructional processes. The intervention integrated differentiated instruction principles with Smart TV-based audio-visual materials, focusing on simple command sentence writing skills. The primary participant demonstrated substantial improvement, progressing from 20% baseline performance to 95% competency after two intervention cycles, representing a 75-percentage-point increase. Class-wide achievement rates improved from 14% to 86% of students meeting minimum competency standards. Observation data revealed enhanced student participation (89% to 97%) and optimal instructional implementation fidelity (94% to 100%) across cycles. The intervention proved particularly effective following strategic refinements including shortened video content and increased individualized support. The findings validate the integration of Tomlinson's differentiation framework with Mayer's multimedia learning theory for slow learner populations. The dramatic improvements support the effectiveness of systematic scaffolding combined with visual-auditory stimulation in addressing working memory limitations and motivational challenges characteristic of slow learners. However, single-participant design and brief intervention duration limit generalizability and long-term effectiveness assessment. Future research should employ larger samples with control groups and extended follow-up periods to establish more definitive evidence for this promising pedagogical approach.